Symptom appraisal, help seeking, and lay consultancy for symptoms of head and neck cancer. Issue 1 (13th July 2017) - Queenan, J.A.; Gottlieb, B.H.; Feldman‐Stewart, D.; Hall, S.F.; Irish, J.; Groome, P.A.
Abstract: Objective: Early diagnosis is important in head and neck cancer (HNC) patients to maximize the effectiveness of the treatments and minimize the debilitation associated with both the cancer and the invasive treatments of advanced disease. Many patients present with advanced disease, and there is little understanding as to why. This study investigated patients' symptom appraisal, help seeking, and lay consultancy up to the time they first went to see a health care professional (HCP). Methods: We interviewed 83 patients diagnosed with HNC. The study design was cross sectional and consisted of structured telephone interviews and a medical chart review. We gathered information on the participant's personal reactions to their symptoms, characteristics of their social network, and the feedback they received. Results: We found that 18% of the participants thought that their symptoms were urgent enough to warrant further investigation. Participants rarely (6%) attributed their symptoms to cancer. Eighty‐nine percent reported that they were unaware of the early warning signs and symptoms of HNC. Fifty‐seven percent of the participants disclosed their symptoms to at least one lay consultant before seeking help from an HCP. The lay consultants were usually their spouse (77%), and the most common advice they offered was to see a doctor (76%). Lastly, 81% of the participants report that their spouse influenced their decision to see an HCP. Conclusions: The results of this study suggest that patients frequently believe that their symptoms were nonurgent and that their lay consultants influence their decision to seek help from an HCP.